New methods in diagnosis and therapyPercutaneous treatment of mitral regurgitation with MitraClip device - Pregowski, Jerzy; Witkowski, Adam (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
The percutaneous edge-to-edge repair of mitral regurgitation with a MitraClip device has been recently approved in Europe. The results of the randomized EVEREST II study showed a favourable safety profile of the technique. However, the efficacy in terms of regurgitation reduction in a population with predominantly degenerative mitral disease was inferior as compared to the results of conventional open heart surgery. Nevertheless, up to 50% of symptomatic heart failure patients with severe mainly functional mitral regurgitation are not treated surgically because of very high procedural risk. The registry data suggest that the minimally invasive and generally well-tolerated MitraClip procedure reduces symptoms and need for recurrent hospitalization and improves left ventricular function in inoperable subjects. The ongoing randomized clinical trials with clinical endpoints will further define the current role of percutaneous edge-to-edge repair in heart failure patients with mitral regurgitation.